Antimicrobial susceptibility patterns of Listeria monocytogenes isolated from fresh produce in KwaZulu-Natal Province, South Africa - Tshabuse, F; Cele, NK; Opoku, AR; Basson, A.; Mthembu, MS; Swalaha, MF (Water S. A., 2024)
Fresh, ready-to-eat produce is frequently irrigated with untreated water, making it a leading cause of foodborne illness outbreaks worldwide. This study investigated the presence of Listeria monocytogenes in fresh produce that was grown using river water. Standard biochemical tests were used for the identification of L. monocytogenes isolated from river water used for irrigation, and from fresh produce including lettuce, spinach, and pumpkin. The inlA gene of L. monocytogenes was molecularly identified using PCR amplification. The susceptibility of L. monocytogenes isolates to antimicrobial agents was assessed using the Kirby-Bauer disc difusion method. The presence of the amplified inlA gene (800 bp) indicated that all of the fresh produce and river water samples were contaminated with virulent L. monocytogenes. Lettuce and spinach exhibited higher quantities of L. monocytogenes, with lettuce recording 87 CFU/g and spinach recording 71 CFU/g. The L. monocytogenes isolates from spinach and lettuce sources showed significant resistance to colistin (56.2% and 53.3%, respectively) as well as ampicillin (68.8% and 53.3%, respectively). Moreover, lettuce (40%) and spinach (31%) exhibited a common resistance pattern of AMP-CHL-CT-KAN-PIP-ERY-TET, with a maximum MAR index value of 0.54. Our research demonstrates the transmission of multidrug-resistant L. monocytogenes from irrigation river water to fresh produce. Hence, the ingestion of ready-to-eat fresh produce carries the potential for human listeriosis, particularly among individuals with compromised immune systems.